A doll's house. - Ibsen,Henrik; Harris, Jed.; Oenslager, Donald, 1902-1975.; Wilder, Thornton, 1897-1975.; Ibsen, Henrik, 1828-1906.; Wilder, Thornton, 1897-1975.; Crothers, Rachel, 1878-1958.; Craven, Frank, 1875-1945.; Lawrence, Gertrude; Broadhurst Theatre (Organization : New York, N.Y.); Theater Playbills and Programs Collection (Library of Congress) (Harare : Weaver, 1938)
The Broadhurst Theatre, Affiliated Theatres Building Co. Inc., Jed Harris presents Henrik Ibsen's "A Doll's House," acting version by Thornton Wilder, settings and costumes by Donald Oenslager, production by Mr. Harris.
The Broadhurst Theatre [New York], beginning Monday evening, February 21, 1938. Matinees Wednesday and Saturday.
Title devised by Library staff.
"The Playbill. The Broadhurst Theatre"--Cover.
Cast: Ruth Gordon, Jessica Rogers, Joseph Olney, Dennis King, Margaret Waller, Paul Lukas, Sam Jaffe, Grace Mills, Lorna Lynn Meyers, Howard Sherman.
LC copy accompanied by playbill advertisement for "Our Town" by Thornton Wilder with Frank Craven at the Morosco Theatre and advertisment for Gertrude Lawrence in "Susan and God" at the Plymouth Theatre.
In: American theater programs of the late 19th and 20th centuries (Library of Congress).
Keywords: Theater programs -- New York (State) -- New York; Theater programs -- 1938.